PERILAKU MEROKOK ANGGOTA KELUARGA DENGAN KEJADIAN BRONKOPNEUMONIA PADA BALITA DI RUANG MARWAH 2RSU HAJI SURABAYA - Dya Sustrami (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2020)
Background: Smoking habits in family members is one of the causes of bronchopneumonia in toddlers. Aim: This study aims to analyze the relationship of smoking behavior of family members with the incidence of bronchopneumonia in children under five in Marwah Room 2 RSU Haji Surabaya. Method: The design of this study was observational analytic with Cross Sectional approach. This research was conducted in Marwah Room 2 Haji Hospital Surabaya in November to December 2019. The sample of this study amounted to 50 respondents. The sampling technique is Simple Random Sampling. Data collection using questionnaire smoking behavior of family members and observation sheets of bronchopneumonia data. Result: The results showed that there were 44 children with severe BP, 6 with BP and 47 with smokers, 3 not smokers. Chi-Square test showed p = 0.035 with a significant level ? <? = 0.05 so that there was a relationship between smoking behavior of family members with the incidence of bronchopneumonia Conclusion: The conclusion of this study is the smoking behavior of family members associated with the incidence of bronchopneumonia in infants, due to lack of awareness of family members about smoking near toddlers and can result in bronchopnea.